Pregnancy in Overt and Subclinical Hypothyroidism and its Feto-Maternal Outcome (Medicine Today, 2014)
This prospective study was done to find out the maternal and fetal complications of pregnancy in patients with subclinical and overt (TSH level higher than subclinical hypothyroidism) hypothyroidism. Chronic hypertension, anemia with GDM, GDM with preeclampsia and thalassemia with GDM were observed only in patients with overt hypothyroidism. PPH, fetal distress, abortion and IUD were significantly higher (p